Usefulness of the skeletal muscle index in postoperative ileus of colorectal cancer patients: a retrospective cohort study - Maho Sasaki; Tatsunari Fukuoka; Masatsune Shibutani; Atsushi Sugimoto; Kiyoshi Maeda; Masaichi Ohira (BMC Surgery, 2022)
Abstract Background Postoperative complications of colorectal cancer mainly include infections (surgical site infection, remote infection, etc.), post-operative ileus (POI), and anastomosis leakage. POI reportedly prolongs the hospital stay and increases medical costs. Therefore, predicting POI is very important. There have been some reports on the relationships between sarcopenia and postoperative complications in colorectal cancer patients, but none have been limited to POI. We therefore conducted a retrospective clinical study with a logistic regression analysis to confirm the risk factors for ileus after colorectal cancer surgery. Methods We retrospectively analyzed 213 patients who underwent elective oncological colorectal surgery for colorectal cancer from November 2017 to July 2021. The skeletal muscle mass (SMM, kg) was estimated using a whole-body bioelectrical impedance analysis (BIA), and the skeletal muscle index (SMI) was calculated as the SMM/height2. We divided all patients into 2 groups based on a low SMI (male < 8.958 kg/m2, female < 8.443 kg/m2) or normal SMI. Preoperative and intraoperative factors as well as, postoperative outcomes were then compared between the two groups. Results The median (range) age of the 213 included patients was 72.0 (33–91) years old. Complications were noted in 96 patients (45.1%), including 21 (9.9%) with POI. There were 68 (31.9%) low SMI patients. POI occurred significantly more frequently in low SMI patients (19.1%) than in normal SMI patients (5.5%) (p = 0.005). In the multivariate analysis, bleeding (p = 0.039) and a low SMI (p = 0.031) were significantly associated with POI. In addition, a propensity score matching analysis was performed to further reduce the selection bias. As a result, a low SMI was the only independent POI predictor among the 78 matched cases. Conclusion A preoperative low SMI in colorectal cancer patients was considered a risk factor for POI.